The Role Of VideoScribe Learning Media In Improving Student Learning Activities - Yasinta Dwi Rahayu (Studi Budaya Nusantara, 2022)
Student learning activities are a series of learning activities that cause changes in learning behavior in students, from not knowing and being unable. Student activity in the learning process is needed to generate high motivation and curiosity. Teachers as facilitators must be able to use learning media that can improve student learning activities, one of the media that can be used is VideoScribe-based learning media to improve student learning activities. The method used in this research is a study of the relevant literature. This study shows that the VideoScribe learning media increases student learning activities and is able to carry out various interactive learning activities. Examples are being active during the learning process, actively reading when given the opportunity to read, actively raising hands when the teacher asks questions, actively giving opinions when given the opportunity to express opinions, and actively asking when given the opportunity. The literature review shows that the VideoScribe learning media is able to increase student learning activities in the learning process. VideoScribe media is recommended for educators, especially in business economics subjects.